Strategi Bertahan Hotel Berbintang dalam Menghadapi Situasi Covid-19 di Kabupaten Badung - I.A Anggreni Suryaningsih; I Gusti Ayu Oka Suryawardani (Pusat Kajian Bali Universitas Udayana, 2021)
The Covid-19 pandemic has had an impact on the tourism industry around the world. In Bali, the impact of the Covid-19 pandemic resulted in the tourism industry, especially the hotel business being very down. Badung Regency, which is a barometer for Bali tourism as well as having the highest number of star hotels in Bali, has been hit hard by the Covid-19 situation. This research data collection method through distributing questionnaires online using google form. The number of star hotels in this study were 30 sample hotels. The samples in this study are grouped into two clusters, namely (1) stars hotel cluster 1,2,3, (2) stars hotel cluster 4 and 5. The results show that the efforts made by star hotels in each cluster are quite diverse, the grouping of these efforts is divided into several categories, among others, marketing, finance, human resources and CHSE-based health protocols.